2006
DOI: 10.1063/1.2209235
|View full text |Cite
|
Sign up to set email alerts
|

Generating long-lasting H1 and C13 hyperpolarization in small molecules with parahydrogen-induced polarization

Abstract: Recently, Levitt and co-workers demonstrated that conserving the population of long-lasting nuclear singlet states in weak magnetic fields can lead to a preservation of nuclear spin information over times substantially longer than governed by the (high-field) spin-lattice relaxation time T1. Potential benefits of the prolonged spin information for magnetic resonance imaging and spectroscopy were pointed out, particularly when combined with the parahydrogen induced polarization (PHIP) methodology. In this contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 14 publications
0
56
0
Order By: Relevance
“…For example, hyperpolarized carbon 13 pyruvate permits high sensitivity detection of tumors in animals. 50 Although the half-life of this improved spin state is typically short, the innovative use of weak magnetic fields 51 and alternative atoms to prolong the effect are exciting avenues of investigation.…”
Section: Hyperpolarization Mrimentioning
confidence: 99%
“…For example, hyperpolarized carbon 13 pyruvate permits high sensitivity detection of tumors in animals. 50 Although the half-life of this improved spin state is typically short, the innovative use of weak magnetic fields 51 and alternative atoms to prolong the effect are exciting avenues of investigation.…”
Section: Hyperpolarization Mrimentioning
confidence: 99%
“…In this case the symmetry is broken only when the parahydrogenated molecule is transferred into a high-field NMR spectrometer. This behavior has been experimentally assessed in parahydrogenated molecules and hyperpolarization storage was observed also when the two parahydrogen protons are coupled to other protons [12,13]. In the latter case it has been shown that three singlet states are formed in proportion of a function of J coupling constants.…”
Section: Introductionmentioning
confidence: 89%
“…In some cases, singlet nuclear spin states have long decay time constants T S which may exceed the spin-lattice relaxation time T 1 by an order of magnitude or more [12][13][14][15][16][17][18][19][20][21]. Such long-lived states have been used to study slow diffusional motion and chemical exchange [16,18].…”
Section: Application To Singlet Nmrmentioning
confidence: 98%
“…Such long-lived states have been used to study slow diffusional motion and chemical exchange [16,18]. Applications are anticipated for transporting and storing hyperpolarized spin order generated by chemical reactions of parahydrogen [19]. The existence of long-lived spin states in systems of more than two coupled spins has been discussed [15,20,21].…”
Section: Application To Singlet Nmrmentioning
confidence: 98%
See 1 more Smart Citation